Corporate Morality: A Systematic Review and Future Research Directions - Subhekti, Erika Fajar; Subhekti, Erick Fajar; Nadia, Fiona Niska Dinda (Graduate Program Magister Manajemen Pendidikan, 2024)
The purpose of this study is to systematically review previous research on corporate morality, which is still under-researched. This research is to fill the literature gap and become a comprehensive understanding of corporate morality in the business environment. This study searched all publications examining corporate morality published from 1988 - 2023. A total of 13 studies from 23 articles were found from the Scopus database. This study found that corporate morality is the moral and ethical principles adopted by a company to direct its business actions and decisions. In addition, the findings of this study also managed to establish several factors that make up corporate morality as antecedents and impacts of corporate morality. However, this literature review only uses 1 database, namely Scopus, so further research can expand the scope of articles reviewed by using other data sources. This research contributes to helping academics and practitioners create more moral business plans.